2016
DOI: 10.3390/metabo6010001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Flux Distribution during Defatting of Steatotic Human Hepatoma (HepG2) Cells

Abstract: Methods that rapidly decrease fat in steatotic hepatocytes may be helpful to recover severely fatty livers for transplantation. Defatting kinetics are highly dependent upon the extracellular medium composition; however, the pathways involved are poorly understood. Steatosis was induced in human hepatoma cells (HepG2) by exposure to high levels of free fatty acids, followed by defatting using plain medium containing no fatty acids, or medium supplemented with a cocktail of defatting agents previously described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Urea is produced by the liver and results from an enzymatic reaction involving carbon dioxide and the ammonia derived from the deamination of proteins in the liver. The increased level of urea suggests increased urea synthesis in defatted livers . Our previously published viability criteria assert that lactate levels <2.5 mmol/L within 4 hours is a major criterion for safe transplantation of ECD donor livers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urea is produced by the liver and results from an enzymatic reaction involving carbon dioxide and the ammonia derived from the deamination of proteins in the liver. The increased level of urea suggests increased urea synthesis in defatted livers . Our previously published viability criteria assert that lactate levels <2.5 mmol/L within 4 hours is a major criterion for safe transplantation of ECD donor livers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies with fat-laden rat hepatocytes and hepatoblastoma cells demonstrated the feasibility of defatting cells with a combination of drugs over 48 hours. (6,18,19) Thereafter, this defatting cocktail was delivered to whole steatotic rat livers during NMP, and the authors demonstrated a decrease in T-TG of 50% within 3 hours. (6) Interestingly, a decrease of 30% could be obtained with NMP alone over the same period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same protocol was later applied to human hepatoma cells (HepG2 cells) by Yarmush et al They found that the cells' lipid content decreased if left in an environment free of FAs. Analysis of metabolites present in the culture media showed that this defatting process was attributed to increased mitochondrial β‐oxidation through upregulation of the tricarboxylic acid and urea cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Additional strategies such as machine perfusion techniques and perfusate selection have been shown to dramatically increase cell yields (52, 53). Moreover, machine perfusion organ reconditioning has proven valuable in improving cell viability and function of ischemic livers and experimentally on fatty livers (5356). Alternatively, the addition of polyethylene glycol to hypothermic preservation solutions has been shown to improve hepatocyte survival following successful isolation (5759).…”
Section: Improving Human Hepatocytes Qualitymentioning
confidence: 99%